Kinerja reksa dana syariah dan beberapa faktor yang memengaruhinya: studi di pasar modal Indonesia 2010-2013 - Setia Mulyawan (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2016)
The purpose of this study was to determine the effect of the characteristics on the performance ofIslamic mutual funds in Indonesia. By analyzing data from 27 Islamic mutual funds traded on theIndonesia Stock Exchange during the 48 months (January 2010-December 2013), and using panel dataas a technical analysis, the study came to the conclusion that the characteristics of Islamic mutual funds,represented by the turnover ratio, expenses ratio, fund size, fund age, and fund selection influence theperformance of Islamic mutual funds in Indonesia. Turnover ratio, fund size, fund age, and fundselection have positive effect to the performance of Islamic mutual fund.